Numerical Treatment of Integral Equations Using Chebyshev Collocation Methods - Ahmed Mohammed Shareef (Universitas Negeri Malang, 2026)
Numerical evaluation of integral equations has become one of the important problems in numerical analysis and computational mathematics, and the calculation of approximate solutions is reduced to solving some systems of linear algebraic equations. In this paper, we will discuss the approximate solutions of linear single integral equations with a Cauchy kernel on a finite interval and Fredholm linear integral equations of the second kind using Chebyshev polynomials. Some numerical examples were presented to illustrate the method.